2014
DOI: 10.15274/inr-2014-10059
|View full text |Cite
|
Sign up to set email alerts
|

Using the Snare System to Cross the Acute-Angled Vertebrobasilar Junction in Treating Posterior Inferior Cerebellar Artery Aneurysm with the Stent-Assisted Method via a Retrograde Approach

Abstract: Retrograde stenting via the contralateral vertebral artery (VA) is a safe and effective treatment for posterior inferior cerebellar artery (PICA) aneurysm. Many methods, including tip shaping and the looping technique, have been attempted as ways to cross the vertebrobasilar (VB) junction. Here, we introduce an alternative method using a Snare system to overcome the acute-angled VB junction after repeated failures using other techniques. The Snare system was navigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Both approaches are advantageous, which is conducive to the placement of the stent and easy embolization of the coil. The retrograde approach to enter the contralateral artery can be guided by using the sheeping technique, 9 and the microguide wire can also be assisted with the snare technique 10 . The retrograde approach can be performed through different communicating arteries, such as the contralateral vertebral artery, as reported by Ecker et al 11 and Cho et al 12 , the internal carotide-anterior communicating artery, as reported by Kwon et al, 13 the carotide-posterior communicating artery as reported by Savardekar et al 14 and the basilar-posterior communicating artery as reported by Cho et al 15 Due to a prolonged procedure time, the incidence of thrombosis is high and increased heparin dosing may increase the relatively high bleeding rate, so it is generally advisable to avoid treating multiple lesions or multiple punctures by concurrent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches are advantageous, which is conducive to the placement of the stent and easy embolization of the coil. The retrograde approach to enter the contralateral artery can be guided by using the sheeping technique, 9 and the microguide wire can also be assisted with the snare technique 10 . The retrograde approach can be performed through different communicating arteries, such as the contralateral vertebral artery, as reported by Ecker et al 11 and Cho et al 12 , the internal carotide-anterior communicating artery, as reported by Kwon et al, 13 the carotide-posterior communicating artery as reported by Savardekar et al 14 and the basilar-posterior communicating artery as reported by Cho et al 15 Due to a prolonged procedure time, the incidence of thrombosis is high and increased heparin dosing may increase the relatively high bleeding rate, so it is generally advisable to avoid treating multiple lesions or multiple punctures by concurrent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As other guiding techniques, Rossen et al 12) reported a hybrid retrograde antegrade approach via the posterior communicating artery for BA occlusion in which it was difficult to cross the lesion. Shin et al 13) reported a method of retaining and pulling the wire by snaring from the contralateral VA for neck bridge stent navigation in coil embolization. This method was not applicable in the present case because the contralateral VA was not antegradely visualized, but it may be effective for acute-phase revascularization.…”
Section: Discussionmentioning
confidence: 99%